UPAYA GURU PEMBIMBING UNTUK MENCEGAH PERILAKU SISWA MENYIMPANG - Adiningtyas, Sri Wahyuni (JURNAL DIMENSI, 2015)
Counselor play a role in preventing aberrant student behavior in school. Conditions such as students who never called for deviant behavior, re-called by often doing the same behavior. Based on the above conditions, suspected the existence of other things that cause a change in the behavior of the students have not ever handled by Counselor. This is likely due to aberrant student behavior prevention efforts conducted by counselor is not optimal. This article reveals that efforts to prevent the Supervising Teacher aberrant student behavior is still lacking as Teacher Advisors is focused on efforts to control deviant behavior. Supervising teachers need to plan and implement service-related BK preventing aberrant student behavior.